Recontextualizing School Improvement Through Education Report Utilization and Teacher Data Literacy Practices - Rini Widyastuti; Nurcahyo Yogyanto; Deny Hadi Siswanto (Pustaka Bangsa Indonesia, 2026)
This study explores the utilization of the Education Report (Rapor Pendidikan) as a strategic instrument for school improvement at SMA Muhammadiyah Mlati. Using a qualitative case study design, data were gathered through in-depth interviews, systematic observations, and documentation studies, subsequently analyzed using the Miles and Huberman interactive model. The findings reveal that while the school has successfully integrated the report into its annual planning (RKS and RKAS) to foster an evidence-based culture, its application remains in a transitional phase. Implementation is currently characterized by surface-level analysis that focuses on general achievements rather than deep root-cause investigations. Although data-driven programs like differentiated learning have emerged, teacher consistency and data literacy remain significant hurdles. Many educators experience technical